How daily negative affect and emotional exhaustion correlates with work engagement and presenteeism-constrained productivity - Ferreira, A. I. (2019)
Exploring productivity loss due to presenteeism and how it can have an influence on employees’ productivity has been an important concern for human resource managers. Using the conservation of resources theory and the job demands-resources model, this study investigated how work engagement could mediate the relationship between both emotional exhaustion and negative affect and productivity loss due to presenteeism in a country experiencing an economic downturn. A total of 42 employees from a health care institution completed a 10-day diary survey (420 diary tasks). Multilevel linear modeling results, including power analyses, showed that negative affect and emotional exhaustion predicted productivity loss due to presenteeism positively, whereas work engagement predicted productivity loss negatively. Furthermore, we found that at a day-level, work engagement mediated the effects of emotional exhaustion and negative affect on productivity loss due to presenteeism. This study highlights the importance of promoting work engagement to reduce the effects of negative affect and emotional exhaustion on productivity loss due to presenteeism through intervention.